Edukasi Ekonomi Sirkular Syariah: Pengolahan Limbah Ikan Menjadi Pakan Ternak Halal - Eny Latifah; Diva Ayu Pramiswari; Aicha Widia Dzilfachriah; Arina Faridatul Mahmudah; Alya Khoioni Muhibbah; Saibatul Fauziyah; Suhailah, Suhailah (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
The high volume of fishery waste often poses an environmental burden if not managed appropriately. Conversely, the circular economy concept offers sustainable solutions aligned with Maqasid Shariah principles in environmental preservation (Hifz al-Alam). This study aims to educate and implement the processing of fish waste into high-quality animal feed that meets halal standards (halalan thayyiban). This research employs a qualitative approach using the Asset-Based Community Development (ABCD) method. The stages include socializing the concept of Sharia circular economy, technical training on waste processing, and nutritional content testing of the feed. The findings indicate an 80% increase in community understanding regarding the economic value of waste. Technically, the fish waste processing successfully produced an alternative animal feed with high protein content, free from najis (impurity) through a purification process according to Islamic jurisprudence (fiqh). This education proves that the integration of circular economy and Sharia principles not only reduces environmental impact but also creates sustainable economic added value for local communities.